History of Dezful City - Samira Bashiri (RIRAI Publisher, 2021)
In the present article, an attempt has been made to present a picture of the city of Dezful and to describe the details of the city and the way of life of the people using first-hand sources, and this description, geographical and historical conditions and type of economy And it encompasses the livelihood of the people and provides an overview of the city of Dezful.